PENGAKUAN DOSA [SOPIR] A[NG]KU[N]TAN PENDIDIK: STUDI SOLIPSISMISH - Achadiar Redy Setiawan; Ari Kamayanti; Aji Dedi Mulawarman (JURNAL PENDIDIKAN AKUNTANSI, 2014)
The mishap in accounting education is often blamed on the philosophy, education system, learning process, and even accounting students.Â  This research explicates that the key to mending accounting education should be triggered by accounting lecturers. Through solipsismish study, we explore our âsinsâ as accounting lecturers with âkejar setorâ/targetting experience-based reflectivity of public transportation driver as metaphor, backed by empirical study of a semester.Â  The hectic schedule of teaching and other activities, not only as lecturers, have given heart-felt impact to students learning process and their attitude.Â  It is urged that accounting lecturers should awaken their consciousness to realize that this profession is not the same asÂ  âsopir angkotâ who are concerned on fulfilling schedules, teaching materials and fee. A concrete solution referring to the Perhimpunan Indonesiaâs agenda proposed in 1925 is needed, which ends in the confirmation of national ideology with some notes